Evaluating critical dispersal rates for whale management under the IWCs Revised Management Procedure: An application for North Atlantic common minke whales - Punt, Andre E.; Van Der Zee, Jurjan P. (J. Cetacean Res. Manage., 2023)
A key consideration for any Revised Management Procedure (RMP) and Aboriginal Whaling Management Procedure (AMWP) Implementation is the choice of stock structure hypotheses, and the weighting of alternative stock structure hypotheses using available data. The RMP/AWMP-lite framework is applied to the North Atlantic common minke whales for three stock structure hypotheses and two RMP ‘variants’. The stock structure hypotheses differ in terms of how many stocks are found in the North Atlantic and how they mix on the feeding grounds. Focusing on the eastern North Atlantic, simulations are undertaken to assess when management performance for two RMP variants is inadequate and how much effective dispersal between adjacent stocks is needed so that the performance of these variants becomes adequate.